Procedural Map Generation by Energy Propagation - Dias, Mauro Victor Pimentel; Franco, Artur de Oliveira da Rocha; Silva, Jose Wellington Franco da; Maia, José Gilvan Rodrigues (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.10173, 2025)
Introduction: Procedural map generation plays a key role in popular game genres such as role-playing games and roguelikes, adding variety and dynamicity that leverages replayability or assists in level design tasks. Objective: We introduce a novel algorithm based on energy propagation for generating maps consisting of connected cells (rooms). Methodology or Steps: Starting from the concept of energy propagation, the algorithm simulates energy distribution across multiple rooms connecting an origin cell to a destination cell. We carried out an extensive experimental evaluation of this algorithm using a two-dimensional grid layout. Results: The algorithm executes in linear time on the number of cells, making it efficient enough to be applied in realtime scenarios. The proposed algorithm can be controlled to yield variable structures, ranging from tree layouts to fully interconnected grids.